1992
DOI: 10.1083/jcb.116.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Carboxy terminally truncated forms of ribophorin I are degraded in pre-Golgi compartments by a calcium-dependent process.

Abstract: Abstract. Two COOH terminally truncated variants of ribophorin I (RI), a type I transmembrane glycoprotein of 583 amino acids that is segregated to the rough portions of the ER and is associated with the proteintranslocating apparatus of this organelle, were expressed in permanent HeLa cell transformants . Both variants, one membrane anchored but lacking part of the cytoplasmic domain (RI,67) and the other consisting of the luminal 332 N112-terminal amino acids (RI332), were retained intracellularly but, in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 67 publications
1
66
1
Order By: Relevance
“…Several polypeptides including the asialoglycoprotein receptor, ribophorin, or T cell receptor subunits are known to be degraded by a nonlysosomal endoproteolytic cleavage that takes place in the ER itself or in ER-derived subcompartments (Amara et al, 1989;Wikstrom and Lodish, 1993;Tsao et al, 1992;Klausner and Sitia, 1990;Bonifacino and Lippincott-Schwartz, 1991). Our observations on thymic epithelial cells show that the ER-Golgi intermediate station is complex and can be induced to expand, in response to the quantity and quality of passenger proteins.…”
Section: Discussionmentioning
confidence: 82%
“…Several polypeptides including the asialoglycoprotein receptor, ribophorin, or T cell receptor subunits are known to be degraded by a nonlysosomal endoproteolytic cleavage that takes place in the ER itself or in ER-derived subcompartments (Amara et al, 1989;Wikstrom and Lodish, 1993;Tsao et al, 1992;Klausner and Sitia, 1990;Bonifacino and Lippincott-Schwartz, 1991). Our observations on thymic epithelial cells show that the ER-Golgi intermediate station is complex and can be induced to expand, in response to the quantity and quality of passenger proteins.…”
Section: Discussionmentioning
confidence: 82%
“…3). A lag phase and biphasic kinetics have also been observed for ER degradation of mammalian secretory proteins (Le et al, 1990;LippincottSchwartz et al, 1988;Tsao et al, 1992). …”
Section: Pra* and Cpy* Show Similar Degradation Kineticsmentioning
confidence: 99%
“…Recent studies on the T-cell receptor have identified the ER itself as the compartment where protein degradation occurs (Stafford and Bonifacino, 1991). A study on a carboxy-terminally truncated version of ribophorin I describes characteristics for the degradative event which indicate the existence of a second, a preGolgi compartment, where proteins in the secretory pathway can be degraded (Tsao et al, 1992). The so-called 'ER degradation' (Lippincott-Schwartz et al, 1988) is not only limited to membrane proteins.…”
mentioning
confidence: 99%
“…Yet, degradation concerns specifically the proteins (both membrane-bound and luminal) that have failed to fold or assemble properly and spares nascent proteins. The lag observed between synthesis and degradation might reflect migration into a specialized subcompartment (Tsao et al, 1992). Whether the latter is physically separated from the ER is doubtful, however, as degradation occurs within permeabilized cells even in the absence of cytosol and ATP, which are essential for vesicular transport (Stafford and Bonifacino, 1991;Wilkstrom and Lodish, 1992).…”
Section: Ca2+ Storesmentioning
confidence: 99%